Azure Security for critical workloads : implementing modern security controls for authentication, authorization and auditing - Lad, Sagar (Apress, 2023)
This is a crisp, practical, and hands-on guide to moving mission-critical workloads to Azure. This book focuses on the process and technology aspects of Azure security coupled with pattern-oriented, real-world examples. You will implement modernized security controls, catering to the needs of authentication, authorization, and auditing, thereby protecting the confidentiality and integrity of your infrastructure, applications, and data. The book starts with an introduction to the various dimensions of cloud security, including pattern-based security and Azure's defense security architecture. You will then move on to identity and access management with Azure Active Directory. Here, you will learn the AAD security model, application proxy, and explore AAD B2B and B2C for external partners. Network security patterns and infrastructure security patterns are discussed next, followed by application and data security patterns. Finally, you will learn how to set up security policies and work with Azure Monitor and Azure Sentinel, and to create leadership support and training for a rigorous security culture. After completing this book, you will understand and be able to implement reusable patterns for mission critical workloads, standardizing and expediting the move of those workloads to Azure.